Porous Ceramic As Basic Contruction Material Based Passive Cooling Clay Mixed With Charcoal Candlenut Shell (AleuritesMoluccana). (May 2020) - Sitorus, Z; Anisah, F; Fauzi
Abstract: It has been made of porous ceramics made of clay with a mixture of candlenut shell activated charcoal through conventional techniques of printing and presses the clay composition variation: activated charcoal shell candlenut 100: 0, 90:10, 80:20, 70:30, 60:40, 50: 50 grams. Clay and activated charcoal candlenut shells sifted with a particle size of 100 mesh. Clay and activated charcoal powder candlenut shells which have been mixed printed by the dry pressing method with the pressure of 5 tons was detained for 10 minutes. Then the beam-shaped sample was burned with a combustion temperature of 900°C and held for 3 hours. Each sample is characterized that include: physical properties (porosity, water absorption, and surface morphology), mechanical properties (hardness, compressive strength, and XRD) and thermal properties (DTA). The results showed that variations in the composition of clay: candlenut shell activated charcoal optimum at 50: 50-gram composition with 66.20% porosity; water absorption value of 69.42%; 298.19 Mpa hardness values; 6, 75Mpa value of the compressive strength and optimum pore diameter 1.0785 μm with oxygen element content of 51.76%. The XRD results showed the addition of activated charcoal on a pecan shell does not form a porous ceramic crystallinity, and from the graph shows that the dominant crystal structure is monoclinic. DTA testing results 70°C and temperature endothermic temperature eksoterm450°C. The XRD results showed the addition of activated charcoal on a pecan shell does not form a porous ceramic crystallinity, and from the graph shows that the dominant crystal structure is monoclinic. DTA testing results 70°C and temperature endothermic temperature eksoterm450°C. The XRD results showed the addition of activated charcoal on a pecan shell does not form a porous ceramic crystallinity, and from the graph shows that the dominant crystal structure is monoclinic. DTA testing results in endothermic temperature 70°C and exotherm temperature 450°C.